2018
DOI: 10.1038/s41419-017-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ζ delivered by hepatocellular carcinoma-derived exosomes impaired anti-tumor function of tumor-infiltrating T lymphocytes

Abstract: Increasing evidence shows that the anti-tumor functions of tumor-infiltrating T lymphocytes (TILs) were inhibited significantly, but the underlying mechanisms remain not fully understood. In this study, we found that 14-3-3ζ expression was up-regulated in hepatocellular carcinoma (HCC) cells and in TILs. TILs with 14-3-3ζ high-expression (14-3-3ζhigh) exhibited impaired activation (CD69), proliferation (Ki67) and anti-tumor functions compared to 14-3-3ζ low expression (14-3-3ζlow) TILs. Flow cytometry assay sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 33 publications
2
94
0
2
Order By: Relevance
“…10,11 It has been proved that ncRNA extracted from exosome could present a stable form to avoid the degradation induced by RNase, indicating they might be mediators for communications in different cells. 13 Various researches have proved that exosome-derived ncRNAs could act as markers for the diagnosis and prognosis prediction in various kinds of human cancers. 13 Various researches have proved that exosome-derived ncRNAs could act as markers for the diagnosis and prognosis prediction in various kinds of human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 It has been proved that ncRNA extracted from exosome could present a stable form to avoid the degradation induced by RNase, indicating they might be mediators for communications in different cells. 13 Various researches have proved that exosome-derived ncRNAs could act as markers for the diagnosis and prognosis prediction in various kinds of human cancers. 13 Various researches have proved that exosome-derived ncRNAs could act as markers for the diagnosis and prognosis prediction in various kinds of human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the EVs, mostly of tumour origin, play a role in the targeting of non-malignant or other cancer cells [56]. A mechanism of these EV effects is immune suppression of lymphocytes, such as CD8 + T, or macrophages [55][56][57][58][59], possibly dependent on the protein 14-3-3ζ over-expressed at the surface of the vesicles [60]. In addition to angiogenesis and metastasis [45][46][47], targeting occurs during cell migration and invasion [53,54].…”
Section: Immune Cell-cancer Cell Interactionsmentioning
confidence: 99%
“…Among biomarkers, some correspond to whole EVs, known to be released from particular cancer cells [45][46][47]; others are based on EV surface proteins, such as tetraspanins and 14-3-3ζ [3,60] or on miRNAs, such as miR-301a-3p and many others, abundant in the lumen of cancer EVs [46,48]. Important for these studies is the identification of biomarkers, useful for the strategy of medical action.…”
Section: Diagnosis and Therapymentioning
confidence: 99%
“…However, depending on the starting material and downstream applications, other methods for the purification and enrichment of HCC-derived exosomes have also been used such as ultrafiltration, size exclusion chromatography (SEC) or the ExoQuick TC method [19,29] . Majority of HCC-derived exosomes have been identified by a combination of different methods including, round or cup shaped morphology by transmission electron microscopy, size of 50-100 nm in diameter by nanoparticle tracking analysis and exosomal surface profiling for markers such the tetraspanins (CD9, CD63, and CD81), heat shock proteins (HSP90 and HSP60), Alix and Tsg101 by immunoblot and flow cytometry [19,20,[29][30][31][32] . Studies have demonstrated high expression of glypican-3 (GPC-3) and AFP, traditional markers of HCC, within the HCC-derived exosomes, thereby confirming the hepatoma-based origin of these exosomes [31] .…”
Section: Isolation and Identification Methods Of Hcc-derived Exosomesmentioning
confidence: 99%
“…For instance, Wang et al [32] demonstrated that 14-3-3ζ, also called 14-3-3 protein zeta was transmitted from HCC cells to T cells via exosomes and resulted in the inhibition of anti-tumour functions of tumour-infiltrating T cells in the HCC microenvironment. HCC-derived exosomes have been shown to be enriched in HCC antigens, which in turn can prime cytotoxic T lymphocytes and elicit a stronger immune response in vitro and in vivo compared with cell lysates [4] .…”
Section: Immune Modulationmentioning
confidence: 99%